2023
DOI: 10.1002/ente.202300051
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐Free Alkali Metal‐Iodide Battery with a Molten Salt

Abstract: in the range of 200-4000 mAh g À1 , and their highly negative redox potential below À2.5 V versus standard hydrogen electrode (SHE) can lead to a high cell operating voltage. These characteristics can enable high specific energies, which are generally given in the unit Wh kg À1 for expressing the energy-storage performance per mass of active materials or the system's total mass. However, the development of rechargeable batteries with alkali and alkaline earth metals has been extremely challenging due to the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 88 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…These two cell designs are based on the previously developed simple cell used for the membrane-free alkali metal-iodide battery (Conductive Cell Body design; Fig. 1c) by Lee et al 40 Further experiments with this early design revealed unstable electrical contact between the glassy carbon crucible and the cell body. In this configuration, the electrical contact relies solely on gravity, making it necessary for both interfaces to be perfectly flat and clean.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These two cell designs are based on the previously developed simple cell used for the membrane-free alkali metal-iodide battery (Conductive Cell Body design; Fig. 1c) by Lee et al 40 Further experiments with this early design revealed unstable electrical contact between the glassy carbon crucible and the cell body. In this configuration, the electrical contact relies solely on gravity, making it necessary for both interfaces to be perfectly flat and clean.…”
Section: Methodsmentioning
confidence: 99%
“…W-HV10S-CE-NI24) were successfully used in Ref. 40. However, for the Na-Zn cell described in this paper the aforementioned feedthroughs are not suitable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation